Microabrasion in tooth enamel discoloration defects: three cases with long-term follow-ups (Journal of Applied Oral Science, 2014)
Superficial irregularities and certain intrinsic stains on the dental enamel surfaces can be resolved by enamel microabrasion, however, treatment for such defects need to be confined to the outermost regions of the enamel surface. Dental bleaching and resin-based composite repair are also often useful for certain situations for tooth color corrections. This article presented and discussed the indications and limitations of enamel microabrasion treatment. Three case reports treated by enamel microabrasion were also presented after 11, 20 and 23 years of follow-ups.